Bangle bracelet / Fatin Nurshaheera Fauzi - Fauzi, Fatin Nurshaheera (2022)
Batik is technique of wax resist dyeing applied to the whole cloth, this technique originated from the island of java, Indonesia. Batik is made either by drawing dots and lines of the resist with a spouted tool called a canting or by printing the resist with a copper stamp called a cap.